Screen citizenship. Information and collective action through the Internet - Ramos Chávez, Alejandro (Revista General de Información y Documentación, 2015)
The rapid changes in information and communication technologies have resulted in other changes that have opened the possibility of analysing and understanding reality in other ways. One of these changes is the way in which individuals obtain and generate information to act in a range of situations, be these of an individual or social nature. In this context, this article is particularly concerned with the need to understand and debate the way in which individuals, by using these technologies, obtain and generate information; organize and interact to generate collective action; and how these interaction mechanisms mould a new type of citizenship, coined by some authors as “digital citizenship”. The article concludes that – while there is relatively wide consensus on the virtues and opportunities that the use of technology represents to facilitate obtaining and generating information, as well as consolidating citizenship participation and strengthening democracy – certain problems considerably hinder their extent and success.